Profitabilitas dalam sektor manufaktur barang konsumsi Indonesia: Investigasi empiris - Aryasa, Hence Made; Fenisa, Delta; Astriana, Giarti; Linanda, Pratika; Sumaryanti, Atin (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2024)
This research aims to investigate the influence of operating cash flow, capital structure, firm size, and ownership structure on the profitability performance of manufacturing companies operating in the consumer goods sector of the Indonesia Stock Exchange. The primary objective is to comprehend the factors that affect a company's profitability in this sector. Using multiple linear regression analysis, the research measures the individual impact of each independent variable on profitability. The sample comprises 24 companies observed during 2019-2021, selected through purposive sampling. The research findings reveal that operating cash flow, capital structure, firm size, and institutional ownership significantly influence the profitability of manufacturing companies in the consumer goods sector.